184k views
5 votes
Use the tools to graph the solution to the equation 6z−27=27 on the number line below.

User BadAtLaTeX
by
5.6k points

1 Answer

3 votes

Answer:

z = 9

Explanation:

To find the solution, undo what is done to z. You can start by adding 27 to both sides of the equation.

6z -27 +27 = 27 +27

6z = 54 . . . . . simplify

Now, you can divide by 6 to make the coefficient of z be 1.

6z/6 = 54/6

z = 9 . . . . . . . simplify

___

The attachment shows a plot of this point on a number line.

Use the tools to graph the solution to the equation 6z−27=27 on the number line below-example-1
User Jhodges
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.